Leptoceridae - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zenodo, 2020)
Family Leptoceridae Triaenodes reuteri McLachlan 1880 —New record for Kyrgyzstan. Range: Kyrgyzstan, United States of America, Norway, Nederland, Germany, Poland, Denmark, Sweden, Finland, United Kingdom, Mongolia, Ukraine, Turkey, Union of Soviet Socialist Republics (Caucasus, Europe, Siberia), Lithuania, Ireland, and Canada (Andersen et al. 1990; Andersen & Wiberg-Larsen 1987; Baijens & Joose 2009; Berlin 2005; Blinn & Ruiter 2009; Botosaneanu & Malicky 1978; Cibaite 2003; Czachorowski & Pietrzak 2004; Gullefors 2008; Ivanov 2011; Panter et al. 2011; Ruiter et al. 2013; Sipahiler 2005; Szczesny & Godunko 2008;). Material examined: Kyrgyzstan, Issyk-Kul Region, Lake Issyk-Kul, Cholpon Ata, Ruh Ordo Cultural Complex, 42°38’49.26”N / 77°05’43.80”E, 26.ix.2011, 4 m#, leg. and coll. İ. K̹ç̹kbasmacı. General Description: Colors of general body, head and mesothorax, and wings light brown, brown, and light brown, respectively. Antennae each consisting of 70 segments; lengths of each antenna and forewing are 18 mm and 7 mm, respectively; tibial spur formula 1, 2, 2; ocelli absent; number of maxillary palp segments 5. Male genitalia (in alcohol): Genitalia light brown. In lateral view (Fig. 1a), abdominal segment IX anterior mar-gin nearly straight and slightly produced anteroventrally; pleural regions except for segment IX each membranous and sparsely setose, the pleural region of segment IX sclerotized and without setae, with slightly convex posterolat-eral margins; sternum IX long, projecting posterad, subquadrate in lateral and ventral views (Figs. 1a, 1b); tergum IX, in dorsal view (Fig. 1c), with rounded posteromesal margin and with dorsomesal papillae not evident. Preanal ap-pendages in dorsal view (Fig. 1c) setose, each with length at least 5 times as long as width, constricted basally, and with blunt apex. Dorsomesal process of tergum X digitate and originating basally, about half as long as tergum X, and with apical setae; dorsal view of tergum X with subparallel lateral margins and apex slightly excavated medially (Fig. 1c); in lateral view (Fig. 1a), subparallel-sided, convex subapicoventrally, straight dorsally, with lateral flange, and with blunt apex, its apicolateral margins with no apparent microtrichia. Inferior appendages each with lateral view (Fig. 1a) subquadrangular and setose with apicodorsal lobe as long as tergum X, heavily setose, blunt apically and apicoventral projection 2/3 as long as apicodorsal lobe, thick, round apically; basodorsomesal process abruptly downturned, subtri-angular, and with blunt apex; in ventral view (Fig. 1b) apicodorsal lobe convex laterally, straight mesally in distal 2/3 to blunt apex; apicoventral lobe also convex laterally and nearly straight mesally, apex acute. Phallus in lateral view (Fig. 1d) with phallobase small, triangular, and highly convoluted, with prominent endothecal membranes, with pair of parameres (subequally long, strongly recurved basally then gently curved, tapering to apices).

Published as part of Küçükbasmaci, İbrahým & Canbulat, Savaş, 2020, A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880), pp. 113-122 in Zootaxa 4896 (1) on pages 115-116, DOI: 10.11646/zootaxa.4896.1.6, http://zenodo.org/record/4359410
Keywords: Insecta; Arthropoda; Trichoptera; Animalia; Biodiversity; Leptoceridae; Taxonomy; 15. Life on land